Serum PINP, PIIINP, galectin-3, and ST2 as surrogates of myocardial fibrosis and echocardiographic left venticular diastolic filling properties - Lepojärvi, E S.; Piira, Olli-Pekka; Pääkkö, Eija; Lammentausta, Eveliina; Risteli, Juha; Miettinen, Johanna A.; Perkiömäki, Juha S.; Huikuri, Heikki V.; Junttila, M J. (Frontiers in Physiology, 2015)
Objectives and Background. Serum biomarkers have been proposed to reflect fibrosis of several human tissues, but their specific role in the detection of myocardial fibrosis has not been well established. We studied the association between N-terminal propeptide of type I and III procollagen (PINP, PIIINP, respectively), galectin-3 (gal-3), soluble ST2 (ST2) and myocardial fibrosis measured by late gadolinium enhanced cardiac magnetic resonance imaging (LGE CMR) and their relation to left ventricular diastolic filling properties measured by tissue Doppler echocardiography (E/e´) in patients with stable coronary artery disease (CAD). Methods and Results. We determined the PINP, PIIINP, gal-3 and ST2 serum levels and performed LGE CMR and echocardiography on 63 patients with stable CAD without a history of prior myocardial infarction. Myocardial late gadolinium enhancement T1 relaxation time was defined as a specific marker of myocardial fibrosis. ST2, PINP and PIIINP did not have a significant correlation with the post-LGE T1 relaxation time tertiles (NS for all), but the lowest post-LGE T1 relaxation time tertile had significantly higher gal-3 values than the other two tertiles (p= 0,002 and 0.002) and higher E/é values (p= 0,009) compared to the highest T1 relaxation time tertile. ST2 (p= 0.025 and 0.029), gal-3 (p= 0.003 and < 0.001) and PIIINP (p= 0.001 and 0.007) levels were also significantly higher in the highest E/é tertile, compared to the other two tertiles. Conclusions. Elevated serum levels of gal-3 reflect the degree of myocardial fibrosis assessed by LGE CMR. Gal-3, ST2 and PIIINP are also elevated in patients with impaired LV diastolic function, suggesting that these biomarkers are useful surrogates of structural and functional abnormality of the myocardium.